2020
DOI: 10.15626/mp.2019.2117
|View full text |Cite
|
Sign up to set email alerts
|

Issues, problems and potential solutions when simulating continuous, non-normal data in the social sciences

Abstract: Computer simulations have become one of the most prominent tools for methodologists in the social sciences to evaluate the properties of their statistical techniques and to offer best practice recommendations. Amongst the many uses of computer simulations, evaluating the robustness of methods to their assumptions, particularly univariate or multivariate normality, is crucial to ensure the appropriateness of data analysis. In order to accomplish this, quantitative researchers need to be able to generate data wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Using this method, previous literature has shown the relatively modest impact of underlying nonnormality on SEM estimates based on polychoric correlations (Flora & Curran, 2004; Li, 2016; Rhemtulla et al, 2012). Thus, in line with previous work examining the impact of underlying nonnormality on ordinal data, we used the Vale-Maurelli method to simulate nonnormal data with a univariate skewness of 2 and univariate kurtosis of 7 to represent “moderate” nonnormality (Curran et al, 1996; Olvera Astivia, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this method, previous literature has shown the relatively modest impact of underlying nonnormality on SEM estimates based on polychoric correlations (Flora & Curran, 2004; Li, 2016; Rhemtulla et al, 2012). Thus, in line with previous work examining the impact of underlying nonnormality on ordinal data, we used the Vale-Maurelli method to simulate nonnormal data with a univariate skewness of 2 and univariate kurtosis of 7 to represent “moderate” nonnormality (Curran et al, 1996; Olvera Astivia, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In order for a multivariate distribution to be nonnormal, either the marginal distributions must be nonnormal or the copula of the multivariate distribution must be nonnormal (Foldnes & Olsson, 2016). The copula of data generated using the Vale-Maurelli method is similar to the multivariate normal copula, and thus the data may not be as nonnormally distributed as intended (Olvera Astivia, 2020). Furthermore, work by Grønneberg and Foldnes (2019) and Foldnes and Grønneberg (2020) has demonstrated that discretizing data produced by the Vale-Maurelli method is numerically equivalent to discretizing the intermediate data generated by the multivariate normal distribution, only with different thresholds.…”
Section: Methodsmentioning
confidence: 99%
“…However, in practice, the normality assumption could also be violated for the variables that underlie the indicators. A plethora of methods exist that could be used to generate underlying nonnormality (e.g., Astivia, 2020;Foldnes & Olsson, 2016). Thus, while LMS-cat and BLMScat have been shown to be robust to the non-normality caused by asymmetrical category thresholds, future research should evaluate their performance with different underlying distributions of the indicators and compare them with other approaches.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…These continuous data are then discretized to produce ordinal data. Using this method, previous literature has shown the relatively modest impact of underlying non-normality on SEM estimates based on polychoric correlations (Flora & Curran, 2004;Li, 2016;Rhemtulla et al, 2012 (Curran et al, 1996;Olvera Astivia, 2020).…”
Section: Underlying Distributionmentioning
confidence: 99%